Globalização excludente, trindade e evangelização, no contexto do Continente Americano - Costalunga, Agnese (2013)
The dissertation on exclusive Globalization, Trinity and evangelization in the context of American continent did emerge that humanity can and must build on the networks of human living together local, national and international, just and fraternal so that everybody can live with dignity. For this to happen ,it is necessary to uproot human coexistence of assaults and encroachments of goods of humanity, through the imposition of brute force, economic, political and social of the few over all mankind, leaving two-thirds of the population excluded from the banquet of life. So it is necessary to create and maintain permanent relationships of equitable justice, recognition of the equal human dignity of all and respect for human rights of all people and peoples of planet Earth. It is not enough to recall principles, state intentions, point to crying injustice and utter prophetic denunciations; these words will lack real weight unless they are accompanied for each individual by a livelier awareness of personal responsibility and by effective action (AO 48). The paradigm of the Triune God reveals to us that to live in the image and likeness of God who created us and saves us, makes us live reciprocal and articulately the anticipation of the historic beginning of life to the final and full to which humanity is called to live. This utopia is always under construction and requires all, continuous efforts of conversion on the way of Emmaus to Jerusalem"(cf.Lk24,33-35).In this walk we can and should build on mutual trust, on responsibility and the on personal and social commitment on a quality of life worthy sustainable for the benefit of every person and every people. The accumulation of unsustainable goods, gradually, always reverts in misery and exclusion of the well-being of others, spreading across the planet and throughout the universe. The Theology through transdisciplinary dialogue with committed entities tries to build up decent life for all, points out ways of conversion for all for the benefit of all. Solidarity with the population excluded from the banquet of Life. assuming it as the subject of change and as a judge to those who live accumulating goods by practicing injustice, denying the fraternity, the communion and the sharing of everything. The ecclesial life exists to be space for the permanent experience of the Reign of God in the humanity and in the world. Exists so that everybody, may walk in communion and in the participation of all, in networks of communion of communities in the world: as global village. The religions and the churches have no other objective to exist other than to celebrate, to collaborate, to incentive, e to witness the presence of the initial historical paradise in the life of each co-brothren. The celebrations and pastoral life celebrate the victory of life over death and announce that in our midst there would be no poor if we practice the commandments of the Lord (cf. Deut15:4-5).